2007
DOI: 10.1007/s10620-007-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ghrelin Levels in Inflammatory Bowel Disease with Relation to Disease Activity and Nutritional Status

Abstract: Ghrelin possesses various biological activities -- it stimulates growth hormone (GH) release, plays a major role in energy metabolism, and is one of the hormones that affects body composition. It also plays a role in modulating immune response and inflammatory processes. In this study we aimed to determine whether serum ghrelin levels had correlation with markers associated with disease activation. We also investigated any probable relationship between serum ghrelin level and nutritional status. Serum levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 40 publications
5
42
0
1
Order By: Relevance
“…This association probably could not be related with activity of the disease. Once it was demonstrated by Ates et al [22] that there was a higher serum ghrelin level in active IBD than in remission disease, and these high levels of circulating ghrelin correlate with the severity and activity of IBD. Similar to our results, Kim et al [23] demonstrated that FD patients with higher plasma levels of fasting ghrelin suffered from less epigastric pain.…”
Section: Discussionmentioning
confidence: 96%
“…This association probably could not be related with activity of the disease. Once it was demonstrated by Ates et al [22] that there was a higher serum ghrelin level in active IBD than in remission disease, and these high levels of circulating ghrelin correlate with the severity and activity of IBD. Similar to our results, Kim et al [23] demonstrated that FD patients with higher plasma levels of fasting ghrelin suffered from less epigastric pain.…”
Section: Discussionmentioning
confidence: 96%
“…13,[32][33][34] Noteworthy, high serum ghrelin levels have been reported in patients suffering from chronic intestinal inflammatory disorders such as ulcerative colitis and Crohn's disease. In these patients increased ghrelin levels correlates with an increase in systemic TNF-a and C-reactive protein.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating gherlin levels in UC and CD patients were positively correlated with sedimentation, C-reactive protein and fibrinogen and negatively correlated with nutritional status parameters (23). It was concluded that gherlin is important in determination of activity in inflammatory bowel diseases (IBD) patients and evaluation of nutritional status.…”
Section: Inflammatory and Infectious Gastrointestinal Diseasesmentioning
confidence: 99%
“…Serum gherlin levels are significantly higher in patients with active ulcerative colitis (UC) and Crohn's disease (CD) than those in remission or controls (21)(22)(23). Circulating gherlin levels in UC and CD patients were positively correlated with sedimentation, C-reactive protein and fibrinogen and negatively correlated with nutritional status parameters (23).…”
Section: Inflammatory and Infectious Gastrointestinal Diseasesmentioning
confidence: 99%